2011
DOI: 10.1002/joc.2170
|View full text |Cite
|
Sign up to set email alerts
|

Present‐day interannual variability of surface climate in CMIP3 models and its relation to future warming

Abstract: ABSTRACT:Interannual variability (IAV) of 2m temperature (T ), sea level pressure (SLP ) and precipitation (P ) in the CMIP3 20th century model simulations are compared with IAV in observational and reanalysis data sets using standard deviation based variability indices. Further, the relation between the representation of T IAV and the amplitude of future warming is investigated. In the Northern Hemisphere (NH) extratropics, T and SLP IAV are (in contrast to P ) in general well represented although a few model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…For climate variables such as land surface temperature and precipitation, we calculate the model variability index (MVI) (Gleckler et al, 2008;Scherrer, 2011). The model (mod) variability at every grid point i is compared against the observed (obs) variability and then averaged over the globe in the following way:…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…For climate variables such as land surface temperature and precipitation, we calculate the model variability index (MVI) (Gleckler et al, 2008;Scherrer, 2011). The model (mod) variability at every grid point i is compared against the observed (obs) variability and then averaged over the globe in the following way:…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The definition of a limit to decide if a model performs well or poor is rather arbitrary. However, Scherrer (2011) and Anav et al (2013) have used a threshold of MVI < 0.5. For a number of carbon-related variables, we calculate the inter-annual variability (IAV), defined as the standard deviation of detrended annual-mean values.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…MIROC is one of the models whose outputs were used in the 4th Assessment Report of the Intergovernmental Panel on Climate Change (IPCC 2007) and several model comparison studies indicate MIROC as one of the best models (Lucarini et al 2006, Scherrer 2010. In particular, Errasti et al (2010) compared IPCC AR4 models performance over the Iberian Peninsula and identified MIROC as one of the 4 best models to simulate the present-day Iberian climate.…”
Section: Meteorological Variablesmentioning
confidence: 99%
“…The numbers of large fires, amount of burnt area and fire severity have lately increased in Portugal (Marques et al 2011, Pereira et al 2011. Despite the severity of the problem, few studies have focused on the effects of climate change on wildfire risk in Portugal (Pereira et al 2002, Durão & Corte-Real 2006, Carvalho et al 2008, 2010. Pereira et al (2005) pointed out that the interannual variability of burnt area in Portugal is largely determined by 2 different atmospheric factors, namely (1) the amount of precipitation during spring (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Before calculating the STD, there is no special filtering applied (Scherrer 2010); that is, interannual variability also contains some decadal variability strictly speaking, although we think the contribution from decadal variability is small. As in the study by Gleckler et al (2008) and Santer et al (2009), we calculate a ''symmetric'' variability statistic (M2), which has the same numeric values for a model that simulates half and twice the observed variability as follows:…”
Section: ) Interannual Variabilitymentioning
confidence: 99%